2022
DOI: 10.1371/journal.pone.0278692
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine acceptability, and uptake among people living with HIV in Uganda

Abstract: Background Despite being a priority population for COVID-19 vaccination, limited data are available regarding acceptability of COVID-19 vaccines among people living with HIV (PLWH) in Sub-Saharan Africa. We described COVID-19 vaccine acceptability and factors associated with vaccine acceptability among PLWH in Uganda. Methods This was a cross-sectional study conducted among PLWH, aged ≥18 years, enrolled participants who were seeking HIV care from six purposely selected accredited ART clinics in Kampala. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…These results suggest high levels of vaccine acceptability and accessibility among pregnant women living with HIV. 47 Our results are similar to those reported in Nigeria where one in five women living with and at risk of HIV had a lower likelihood of being vaccine-hesitant. 48…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results suggest high levels of vaccine acceptability and accessibility among pregnant women living with HIV. 47 Our results are similar to those reported in Nigeria where one in five women living with and at risk of HIV had a lower likelihood of being vaccine-hesitant. 48…”
Section: Discussionsupporting
confidence: 90%
“…These results suggest high levels of vaccine acceptability and accessibility among pregnant women living with HIV. 47 Our results are similar to those reported in Nigeria where one in five women living with and at risk of HIV had a lower likelihood of being vaccinehesitant. 48 For this study, data collected over 13 months shows that there was a modest increase in vaccination uptake among study participants from 0.4% at the beginning of the study in September 2021 to 2.6% at the end of the study in September 2022.…”
Section: Vaccine Uptake Over Timesupporting
confidence: 90%
“…Conversely, this prevalence is slightly lower than a prevalence of 72.7% which was reported in Kampala Uganda by (21). Another study done in Ireland reported that 72% of their participants were willing to receive COVID-19 vaccine (22).…”
Section: Discussionmentioning
confidence: 74%
“…This group of individuals may be ideal for focused vaccination campaigns, as results from this study suggest that PLWH were more likely to perceive vaccines as safe and effective and trust government regulatory processes. A survey among PLWH in Uganda similarly found high levels of trust in government officials and significant willingness for COVID-19 vaccines [ 38 ]. This is likely because PLWH on chronic therapy interact with the public healthcare system often and have come to trust in and rely on the services.…”
Section: Discussionmentioning
confidence: 99%